Modifications of the nucleoprotein of viral haemorrhagic septicaemia virus showed gain of virulence in intraperitoneally infected rainbow trout. Issue 9 (18th May 2021) - Alencar, Anna Luiza Farias; Kwon, Se Ryun; Rasmussen, Thomas Bruun; Mérour, Emilie; Olesen, Niels Jørgen; Cuenca, Argelia
Abstract: Viral haemorrhagic septicaemia virus (VHSV) is the cause of an important listed disease in European rainbow trout ( Oncorhynchus mykiss ) aquaculture and can be present in a wide range of fish species, including marine fish, which can act as viral reservoir. Recent studies revealed putative genetic virulence markers of VHSV to rainbow trout highlighting the roles of the nucleoprotein, phosphoprotein and non‐virion protein. Using reverse genetics, we produced recombinant viruses by introducing parts of or the entire nucleoprotein from a high‐virulent isolate VHSV into a low‐virulent backbone. Furthermore, we also made recombinant viruses by introducing residue modifications in the nucleoprotein that seem to play a role in virulence. Rainbow trout challenged with these recombinant viruses (rVHSVs) by intraperitoneal injection (IP) developed clinical signs and showed lower survival when compared to the parental rVHSV whereas fish challenged by immersion did not show clinical signs except for the high‐virulent control. The mutations did not influence the viral growth in cell culture. The recombinant viruses and parental recombinant were unable to replicate and show cytopathic effect in EPC cells whereas the high‐virulent control was well adapted in all the fish cell lines tested. We showed evidence that corroborates with the hypothesis that the nucleoprotein has virulence motifs associated with VHSV virulence in rainbow trout.